Using Artificial Intelligence to Determine the Impact of E-Commerce on the Digital Economy - Dumiter, Florin Cornel; Schebesch, Klaus Bruno (Journal of theoretical and applied electronic commerce research, 2025)
E-commerce indicators are very complex and have a wide range of levels of complexity and applications. The digital economies that we are oriented towards also have complex features in terms of consumers and businesses. The research objectives are focused on determining the impact of e-commerce on the digital economy within countries with different stages of economic development, digitalization techniques, and e-commerce usage. This study evaluates how AI-based clustering reveals patterns in the e-commerce indicators influencing the digital economy. The research methods used are focused on AI techniques in order to evaluate and assess the usage of e-commerce in the digital economy. In this sense, the methods used in this research are clustering techniques in order to determine the stage of implementation of the digital economy. The research implications have a worldwide impact and soundness in establishing the evolution of the e-economy in different types of countries with different stages and levels of digitalization and different e-commerce development paths. The empirical results show there are significant differences between countries due to cultural, economic, social, and judicial differences. The conclusions of this study highlight that using AI techniques can be a solution for enhancing future digital economy development and labor market consolidation, especially by strengthening e-commerce indicator usage and application.